Pengisbatan al-Imamah Melalui al-Bada’ menurut Syiah al-Ithna `Ashariyyah: The Affirmation of Imamate Through Al-Bada’ According to the Shiite a-Ithna `Ashariyyah - Ismail, Mohd Hamidi; Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
Al-bada’ which denotes a meaning of ‘distinct or clearer than before’, was first introduced by the followers of Shiite al-Ithna ‘Ashariyyah to affirm the imamate in accordance with their thought. They affirmed that God knew best the needs and interests of the imamate which were previously unknown. This was due to the realization that if they were merely guided by the proclamation of scripture and testament, their claims of the twelve chosen imamate would be contradicted to the original concept of the imamate that had been held earlier by the Shiite al-Imamiyyah school of thought. Subsequently, the Shiite al-Ithna ‘Ashariyyah detached from upholding the supremacy of Ahl al-Bayt. Their claims have in fact violated the understanding as expressed in the Holy Qur’an and the Sunnah as well as in the consensus of the majority of Muslims. This is summed up in the present article that the affirmation of imamate through al-bada’ which alledgedly for the benefits of men is fallacious as well as would impair the perfection of God Al Mighty.